Anthropocentric text typology models - Margarita K. Pak, Gulya M. Khairova, Galina Y. Amanbaeva, Larissa M. Kharitonova, Lyubov R. Shevlyakova, (Opción)
The article presents an analysis of theoretical concepts and applied communication models. The purpose of the article is to substantiate and identify ontological features and distinctive parameters of texts of various functional and stylistic characteristics. The research methodology is oriented towards an anthropodeterministic understanding of the nature of the text and the mode of its functioning. The main results are modeling ontological parameters of the text from the position of a functional understanding of the text as a process and product of communication. The article explores relevant concepts and theories of communication and identifies invariant and variable parameters of the functioning of texts in the projection of extralinguistic variables.